SUSTAINABLE SUPPLY CHAIN PRACTICES AND THEIR IMPACT ON COMPETITIVE ADVANTAGE: EVIDENCE FROM INDONESIA’S MANUFACTURING SECTOR - Syarkani, Yofy (UIN Sunan Gunung Djati Bandung, 2025)
This study explores the relationship between sustainable supply chain practices (SSCP) and competitive advantage within Indonesia’s manufacturing sector through a structured literature review approach. As global industries face mounting pressure to integrate environmental and social considerations into their operations, the need for sustainable supply chain strategies has become increasingly critical. Despite a growing body of literature, empirical insights specific to Indonesia’s manufacturing context remain fragmented and underexplored. This paper synthesizes existing research to identify key dimensions of SSCP environmental management, ethical sourcing, and circular logistics and their strategic relevance to competitiveness. Using data extracted from peer-reviewed sources indexed in Scopus and other academic databases, the study applies a narrative review method to consolidate findings. The results indicate that firms adopting sustainable practices tend to achieve improved brand reputation, cost efficiency, regulatory compliance, and innovation capacity. Furthermore, the integration of sustainability into supply chains enhances long-term resilience and stakeholder trust. However, challenges persist, including lack of infrastructure, limited awareness, and regulatory inconsistency in the Indonesian context. This review not only bridges theoretical perspectives but also offers practical implications for policymakers and industry leaders. It concludes by highlighting research gaps and proposing future directions to advance sustainable supply chain scholarship in emerging economies.